2010
DOI: 10.1177/1368430209350747
|View full text |Cite
|
Sign up to set email alerts
|

Believing shapes seeing: The impact of diversity beliefs on the construal of group composition

Abstract: Previous research has suggested that diversity effects depend on how group members perceive their group’s composition. However, what determines how diversity is perceived is unclear. We argue that the way in which group members construe their group’s diversity is shaped by group members’ beliefs about the value in diversity. Focusing on groups with objective subgroups, we show in two studies that the more group members value diversity, the more likely they are to construe their diversity in terms of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 54 publications
(114 reference statements)
6
136
3
2
Order By: Relevance
“…This finding is in line with Joshi and Roh's (2009) proposition that contextual effects should always be taken into account when studying the effects of team diversity. Our findings therefore not only corroborate a moderator-approach to diversity and faultline research (e.g., Homan, Greer, & Koning, 2010), but also speak in favour of multilevel approaches to organizational phenomena (Kozlowski, 2012). The finding that team diversity affects different team members in different ways also …”
Section: Discussionsupporting
confidence: 80%
“…This finding is in line with Joshi and Roh's (2009) proposition that contextual effects should always be taken into account when studying the effects of team diversity. Our findings therefore not only corroborate a moderator-approach to diversity and faultline research (e.g., Homan, Greer, & Koning, 2010), but also speak in favour of multilevel approaches to organizational phenomena (Kozlowski, 2012). The finding that team diversity affects different team members in different ways also …”
Section: Discussionsupporting
confidence: 80%
“…Homogenity is the other dimension (along with hierarchy) theorized to be the most important and ubiquitous property of groups (Gruenfeld & Tiedens, 2010), and research has recently demonstrated that perceived diversity can have important effects on teams, independent of objective diversity (Homan, Greer, Jehn, & Koning, 2010;see Shemla et al, 2014 for a review). According to the SEA model, visual perceptions of homogeneity should influence judgments of group homogeneity or diversity.…”
Section: Impressions Of Group Homogeneity and Diversitymentioning
confidence: 99%
“…Team members with similar work values are more willing to obey the norms of teamwork, reconcile differences, and reduce any tensions during interpersonal interactions (Homan et al, 2010;Nemeth and Staw, 1989). In contrast, when team members have different values, friction results and increases the extent of relationship conflict among team members (Liang et al, 2007).…”
Section: Hypothesesmentioning
confidence: 99%